Tritium measurements by nuclear reaction analysis using 3He beam in the energy range between 0.7 MeV and 5.1 MeV. (September 2021) - Markelj, S.; Payet, M.; Bernard, E.; Lipoglavšek, M.; Kelemen, M.; Cvetinović, A.; Grisolia, C.; Pelicon, P.
Highlights: Production of stable tritiated sample. Detection of reaction products from nuclear reaction between tritium and 3-helium. Establishment of a new nuclear reaction analyzing method for tritium detection via 3-helium beam. Review of the existing literature on the nuclear reaction between 3He and 3H. Abstract: A solid thick tritiated W sample was produced in order to probe the efficiency of detecting tritium via 3 He ion beam using nuclear reactions analysis (NRA). Extensive literature search showed that there were only a few measurements done more than sixty years ago using the reaction with 3 He. Their aim was mainly to measure the absolute cross section of the reaction. In order to use this reaction as an analysing tool for low level radioactive waste we need the differential cross section at certain angles. Using a thick tritiated W sample we measured the NRA signal in the 3 He energy range from 0.7 MeV to 5.1 MeV and we have detected reaction products with energies between 6.5 MeV and 9.75 MeV that were not present on a deuterated W sample prepared in the same manner. This NRA signal proved to be due to deuterium and protons coming from the nuclear reaction between tritium and 3 He. The detection signal increased with 3 He energy up to 3.4 MeV and decreased with energy at the highest beam energies. At higher energies particles from W and target impurities start to disturb the measurement. Their origin might be due to other nuclear reactions, for example between 3 He and W or 3 He with 13 C or 14 N.